Preparation and Characterization of Glucosamine Nanoparticle by Ionic Gelation Method Using Chitosan and Alginate - Yuli Agung Prasetyo; Taofik Rusdiana; Marline Abdassah (Indonesian Journal of Pharmaceutics, 2019)
Osteoarthritis is a chronic degenerative disease of the joints that usually treated by NSAID drugs in the long term leading to cardiovascular and gastrointestinal disorders. Glucosamine is a precursor in the formation of progression of joint which have not a significantly side effect. The problem in glucosamine administration occured when it is administered through the oral route resulting in first pass metabolism, while when it is administered via intavena route resulting in insulin resistance. Those problems can be solved by developing glucosamine into nanoglucosamine in order to increase the enzymatic stability which will protect the active ingredient from diminishing by the first pass effect hence the dose can be reduced, consequenlty it will reduce the insulin resistance, and increase the permeation. In this study, the nanoparticles of glucosamine with chitosan polymer and crosslinker alginate was prepared by the ionic gelation method with the principle of continued cross forming polyelectrolyte complexes. This study started from preformulation such as solubility and identify study by FTIR, then the formulations of chitosan: glucosamine: alginate = 5:1:1 (volume ratio) with the variation of concentration in the FI (chitosan: glucosamine: alginate = 0.08 %: 0.1%: 0.08%) and FII (chitosan: glucosamine: alginate = 0.1%: 0.1%: 0.08%). Results of nanoparticle characterization by particle size analyzer in the FI showed the better formula indicating a foggy coloid, no precipitation, the pH was 2.90±0.05, and the percent transmittance was  99.35%. The distribution of particle size, polydispersity index, and zeta potential for the formula I were 76.0 ± 21.8 nm; 0.300; and -0.30 mV, respectively. It could be concluded that the nanoparticle system of glucosamine can be better prepared from the 0.08% of chitosan, 0.1% of glucosamine and 0.08% of alginate.Keywords: alginate, chitosan, ionic gelation method, glucosamine nanoparticle